How to attract tourists in the European Union? - Simionescu, Mihaela (Revista de turism - studii și cercetări în turism, 2021)
The objectives of this paper are to identify some determinants of tourism arrivals in the European Union (EU-28) countries and propose other constructs based on these factors. The determinants of tourism arrivals in the European Union (EU-28) countries as destination were analyzed using two econometric techniques: panel data models and Bayesian models in the stochastic search variable selection. According to panel data approach, number of employed persons in tourism, net occupancy rate in hotels and in the same type of accommodation and number of establishments had a positive influence on total tourist arrivals and on non-resident tourist arrivals over 2017-2019. For resident tourists, the number of establishments was not relevant in explaining their arrivals in European Union countries. According to Bayesian approach, in 2017, 2018 and 2019 the inflation affected the tourist decisions of arrival in European Union, even if they are resident or non-resident in a certain EU-28 country. In 2017 and 2019 for resident people and in 2018 for non-resident people, the tourists preferred less safe zones, probably because they appreciated more the touristic potential. It is clear that more establishments will ensure more tourism arrivals in European Union.